2012
DOI: 10.2111/rem-d-11-00100.1
|View full text |Cite
|
Sign up to set email alerts
|

Does Cattle Grazing Affect Ant Abundance and Diversity in Temperate Grasslands?

Abstract: Half of the world’s land base is grazed by domesticated livestock. Because of the important functional role of ants in grasslands, it is important to understand the effect of livestock grazing on ant abundance and diversity. The objectives of this study were to examine the effect of cattle grazing and site productivity on the abundance, species richness, and species diversity of ants in Lac du Bois Grasslands Provincial Park, British Columbia, Canada. We hypothesized that the measured ant variables would be lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…The lower carabid diversity we found with grazing is inconsistent with Dennis et al (2002) who found a higher diversity of arthropods in moderately grazed areas, and Crisp et al (1998) who found high beetle diversity in modified (disturbed) habitats. Schmidt et al (2012) found higher ant abundance and diversity in grazed sites but only at high productivity sites; ant abundance and diversity were reduced by grazing in low productivity sites. Cagnolo et al (2002) determined that carabid diversity was reduced by heavy grazing in Argentinean montane grasslands.…”
Section: Discussionmentioning
confidence: 81%
“…The lower carabid diversity we found with grazing is inconsistent with Dennis et al (2002) who found a higher diversity of arthropods in moderately grazed areas, and Crisp et al (1998) who found high beetle diversity in modified (disturbed) habitats. Schmidt et al (2012) found higher ant abundance and diversity in grazed sites but only at high productivity sites; ant abundance and diversity were reduced by grazing in low productivity sites. Cagnolo et al (2002) determined that carabid diversity was reduced by heavy grazing in Argentinean montane grasslands.…”
Section: Discussionmentioning
confidence: 81%
“…Local differences in precipitation, temperature, soil depth and texture, soil parental material, topography, and aspect contribute to the structure and composition of local plant and animal communities [ 27 29 ]. Dominant grasses include bluebunch wheatgrass ( Pseudoroegneria spicata (Pursh) A.Love) and rough fescue ( Festuca scabrella Rydb.).…”
Section: Methodsmentioning
confidence: 99%
“…Many factors affect composition and distribution of ant species, including natural succession (Costa et al 2010), climatic change (Kwon et al 2014) and other anthropogenic impacts on forest ecosystems (e.g. logging and livestock grazing; Schmidt et al 2012;Frank et al 2015). As most ant species used by Apennine brown bears are found in open and sun-exposed sites, forest clearings, early stages of forest succession, grasslands and ecotones should be actively managed accordingly.…”
Section: Discussionmentioning
confidence: 99%